Answer :

nCr + nCr+1 = n+1Cx (Given)


Now, we have


nCr + nCr-1 = n+1Cr (1)


From (1) and (Given) we have,


n+1Cr+1 = n+1Cx


r + 1 = x ( nCx = nCy n = x + y or x = y )

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that the prRD Sharma - Mathematics

There are 10 lampMathematics - Exemplar

If n+1RS Aggarwal - Mathematics

If nC<RS Aggarwal - Mathematics

Fill in the BlankMathematics - Exemplar

Fill in the BlankMathematics - Exemplar

The number of wayMathematics - Exemplar

Total number of wMathematics - Exemplar

The number of wayMathematics - Exemplar

The number of triMathematics - Exemplar